Clinical profile of vitiligo patients and relationship with immuno-inflammatory markers - Marta Regina Machado Mascarenhas; Mariana de Castro Oliveira; Luise Fonseca de Oliveira; Andréa Santos Magalhães; Paulo Roberto Lima Machado (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Vitiligo is the most common pigmentary disorder and is considered a chronic, cumulative, multifactorial disease. The crucial role of cytotoxic CD8+ T lymphocytes and the IFNγ/CXCL10 axis has been demonstrated in its pathogenesis. Objective To evaluate the clinical profile and immuno-inflammatory markers in patients with vitiligo in a reference medical center. Methods Cross-sectional study in which all patients with vitiligo seen at the medical center the from 2019 to 2022 were evaluated, to outline the clinical profile. Moreover, cardiovascular risk biomarkers (neutrophil/lymphocyte ratio and C-reactive protein levels) were measured, as well as cytokines and chemokines (TNFα, IFNγ, IL10, IL15 and CXCL10) in the serum of a subgroup of 30 patients. Results There was a predominance of females, with a mean age of 43 years. Most were phototypes IV or V (71.3%), without comorbidities (77.55%), and without a family history of vitiligo (70.41%). Higher levels of neutrophil/lymphocyte ratio, C-reactive protein, and inflammatory cytokines/chemokines were documented in vitiligo patients when compared to the control group (non-significant). As relevant data, the highest values of CXCL10 were detected in patients with vitiligo versus controls, as well as in patients with disease of shorter duration (p < 0.05). Study limitations The number of assessed patients was small due to recruitment difficulties caused by the COVID-19 pandemic. Conclusion The present data contribute to confirming the relevant role of the IFNγ/CXCL10 axis in the pathogenesis of vitiligo, highlighting CXCL10 as a possible activity marker.